2020
DOI: 10.21037/cdt.2019.11.07
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of cardiac CT integrated with FFRCT for planning myocardial revascularization in complex coronary artery disease: a lesson from SYNTAX studies

Abstract: After two decades of clinical use, during which coronary CT angiography (CCTA) was considered an appropriate method for the non-invasive assessment of patients with suspected stable coronary artery disease (CAD) and low-to-intermediate pretest likelihood of CAD, a growing body of literature is showing that CCTA may have also a clinical role in patients with high pretest likelihood of CAD, known CAD and complex and diffuse CAD. Particularly, the SYNTAX studies demonstrated the usefulness of CCTA in the field of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The SS is primarily based on the location, type, and number of coronary artery lesions, providing robust theoretical support for the choice between PCI and Coronary Artery Bypass Grafting (CABG) [ 31 , 32 ]. Studies have demonstrated that SS can predict the prognosis of patients undergoing PCI or CABG, offering a significant theoretical basis for evaluating the severity and prognosis of coronary heart disease [ 33 ]. High-sensitivity Troponin T (HS-TnT) is a highly specific biomarker for myocardial injury assessment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SS is primarily based on the location, type, and number of coronary artery lesions, providing robust theoretical support for the choice between PCI and Coronary Artery Bypass Grafting (CABG) [ 31 , 32 ]. Studies have demonstrated that SS can predict the prognosis of patients undergoing PCI or CABG, offering a significant theoretical basis for evaluating the severity and prognosis of coronary heart disease [ 33 ]. High-sensitivity Troponin T (HS-TnT) is a highly specific biomarker for myocardial injury assessment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation and risk classification of individuals who come with chest discomfort is now its primary purpose. While this is undoubtedly the most prevalent utilization of this technique, it may also be a useful complement in other contexts, including plaque evaluation, coronary artery stenosis functional evaluation, and complicated intervention planning [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first study that addressed the safety and feasibility of using CCTA-FFR alone for treatment decision-making was the FASTTRACK CABG trial (2020), which evaluated the use of CCTA-FFR for planning surgical revascularization in patients with complex coronary artery disease; the surgeons reported that this modality was safely applicable for management of patients without ICA in 84% of cases [ 107 ]. In addition to the confirmed usefulness of CCTA-FFR in diagnosing and managing CAD, compared with ICA-FFR [ 108 ], other advantages have also been elaborated for this novel method, including reduced cost and improved patients’ quality of life [ 109 , 110 ]. Nevertheless, this method is also not exempt from limitations, elaborated further below.…”
Section: Clinical Implication Of Ccta-ffr Vs Ica-ffrmentioning
confidence: 99%